Pension Finance Literacy of Indian Government Employees with Respect to the National Pension Scheme - Aggarwal, Shruti; Khanna, Ashu (Arthshastra Indian Journal of Economics & Research, 2021)
Pension finance literacy of individuals in India is still at a nascent stage owing to low interest and lack of awareness in this sector. The Government of India, in 2004, introduced the National Pension Scheme for government employees in place of the Old Pension Scheme. A survey was done to examine employees’ awareness about the new scheme and understand whether they were aware of the various features of the scheme. The survey included a questionnaire designed specifically for government employees and included questions regarding the scheme’s features and characteristics. Another aim of the survey was to inspect the satisfaction level of the people from the new scheme. The participants included Central and State government employees. Analysis of the results was done using t-test and ANOVA. The effect of demographic variables such as education, gender, income, and marital status on government employees’ pension finance literacy was measured. The results revealed the mixed response of employees. Although a good number of people were found to be aware of the various aspects of the scheme, demographic variables majorly affected the awareness level. Employees were found to be dissatisfied with the scheme’s performance. People wanted some changes in the scheme in aspects such as withdrawal and taxation and generally thought that the scheme was not employee-friendly. Based on the discussion with employees, some suggestions have been put forward so as to make the scheme more alluring.